До питання про розвиток інноваційної діяльності Гарвардської медичної школи у 1780–1860 рр. - Куліченко, Алла Костянтинівна; Kulichenko, Аlla (Сумський державний педагогічний університет імені А. С. Макаренка, 2020)
Стаття присвячено огляду розвитку інноваційної діяльності в Гарвардській медичній школі з 1780-х рр. до 1860-х рр. Визначено, що Гарвардську медичну школу заснували в 1782 р., а освітній процес спочатку забезпечували три професори – Дж. Воррен, Б. Вотерхауз та А. Декстер, зібравши потужну на той час матеріально-технічну базу. З’ясовано, що перші випускники отримали ступінь бакалавра медицини і їм було запропоновано отримати ступінь доктора медицини. До вагомих інноваційних здобутків Гарвардської медичної школи або Массачусетського медичного коледжу (така назва була в 1820–1880 рр.) окресленого періоду належать такі: вакцинація від віспи, анестезія за допомогою оксиду азоту, відкриття нових посад та кафедр, ухвалення анатомічного закону тощо. Despite the opening of the Harvard Medical School in the 1780s, the innovative activity of this medical school was impressive. It should be mentioned that the innovative activities at the Harvard Medical School were both collective and individual. Thus, the article deals with a review of innovative activity development in the Harvard Medical School from the 1780s to the 1860s. The chronological boundaries of the study include such periods: the 1780s – opening of the Harvard Medical School and the origins of the educational process for the training of future physicians; the 1860s – the period of the Civil War and the beginning of Charles Elliot’s presidency at the Harvard University, which marked a new milestone in the development of medical education. To achieve the article aim, we have used the following methods: analysis and systematization of scientific and pedagogical sources (annual reviews, circulars, articles) and information resources (official website of Harvard Medical School); structural-logical and historical-genetic methods – to represent a holistic view of the innovative activities of the Harvard Medical School, highlighting its features in the period from the 1780s to the 1860s. The Harvard Medical School was founded in 1782, and initially three professors – J. Warren, B. Waterhouse, and A. Dexter – were providing the educational process by gathering a powerful material and technical base at that time. Besides, the first graduates got a bachelor degree in medicine and were offered a doctorate in medicine. Significant innovative achievements of the Harvard Medical School or Massachusetts Medical College (this name was in the 1820s–1880s) included the following: smallpox vaccination, nitric oxide anesthesia, opening of new positions and departments, adoption of anatomical law, etc. Educational, organizational, methodological, scientific activity and public position of the teaching staff were permeated with innovations, both successful and poor ones. However, poor innovations became starting points for improvement and inspiration for further fruitful work due to the economic, political situation and urgent needs of society. As for future research, we aim to describe the origins of innovative activity in American medical education on the examples of Columbia University College of Physicians (New York), Dartmouth Medical College, and University of Maryland School of Medicine.
To the issue of innovative activity development of the Harvard Medical School during the 1780s–1860s
Keywords: американська медична освіта; інноваційна діяльність; Гарвардська медична школа; Массачусетський медичний коледж; бакалавр медицини; доктор медицини; кафедри; щеплення від віспи; анестезія; анатомічний музей Воррена; American medical education; innovative activity; Harvard Medical School; Massachusetts Medical College; Bachelor of Medicine; Doctor of Medicine; departments; smallpox vaccination; anesthesia; Warren Anatomical Museum